Development And Validity-Reliability Testing Of An Early Childhood Education Institution Performance Instrument Based On A Psychometric Approach - Melati Indri Hapsari; Ani Rusilowati; Nina Oktarina (Proceedings of International Conference on Science, Education, and Technology, 2026)
This study aimed to develop and examine the validity and reliability of a psychometric-based performance instrument for Early Childhood Education (ECE) institutions. The study employed a Research and Development (R&D) method using a quantitative psychometric approach. Instrument development was conducted through several stages, including construct identification, indicator formulation, expert validation, instrument trials, and statistical validity-reliability testing. The instrument was developed based on four dimensions of institutional performance: input, process, output, and outcome, consisting of 30 statement items using a Likert scale. The research sample involved 300 teachers and administrators of ECE institutions. Content validity was analyzed using Aiken’s V index, construct validity was tested through Exploratory Factor Analysis (EFA), and reliability was measured using Cronbach’s Alpha coefficient. The results showed that all instrument items met the validity criteria, with Aiken’s V values ranging from 0.80 to 0.90 and factor loading values above 0.50. The Kaiser-Meyer-Olkin (KMO) value exceeded 0.50, and Bartlett’s Test of Sphericity was significant, indicating the feasibility of factor analysis. The reliability test produced a Cronbach’s Alpha value of 0.973, indicating very high internal consistency. Therefore, the instrument was declared valid, reliable, and feasible for evaluating ECE institutional performance. Keywords: early childhood education; institutional performance instrument; psychometric approach; validity and reliability testing